A comparative study of two Mobile Mental Health Units in different catchment rural areas in Greece. (March 2022) - Peritogiannis, Vaios; Rousoudi, Sofia; Vorvolakos, Theofanis; Gioti, Panagiota; Gogou, Afroditi; Arre, Argiri; Samakouri, Maria
Background: Mental healthcare service delivery in rural and remote areas in Greece is challenging due to socioeconomic and geographical reasons, and distant facilities. To address the needs of the underserved areas, the Greek state has launched a number of Mobile Mental Health Units (MMHUs). Aim: The objective of the present study was to explore the differences among two MMHUs, one being run by a university general hospital (MMHU UHA) and the other being run by a nongovernmental organization (MMHU I-T). Methods: The two MMHUs deliver services in rural areas of northeast and northwest Greece, respectively. Both MMHUs use the infrastructures of the primary healthcare system and have the potential for domiciliary visits. Results: Medical and nursing staff is much more in the MMHU UHA, whereas MMHU I-T has more psychologists, social workers and health visitors. Patients attended the MMHU I-T were significantly older than the patients attended the MMHU UHA (mean age 64.5 vs. 55.3 years) and the percentage of the elderly patients in treatment with the MMHU I-T (56.5%) is significantly higher than the corresponding percentage of the MMHU UHA (20%). The proportion of patients that received home-based care by the two MMHUs was almost identical. The percentage of patients with schizophrenia spectrum disorders that attended the MMHU UHA was significantly higher. Patients with affective disorders, anxiety disorders and organic brain disorders that attended the MMHU I-T were significantly more. Conclusions: Despite the similarities among the MMHUs in rural Greece, this study recorded some important differences. The differences in staffing may be accounted for by the availability of resources. The differences in the patients' population may be explained by the fact that the MMHU UHA was designed from its beginning to treat patients with severe mental illnesses, mainly psychoses, and it accepts loss of referrals within the general hospital's network of psychiatric services. The MMHU I-T is an independent, locally based service that may be better perceived as an expansion of the primary care system. The results of the study could inform service practice and mental health policy.